DAMPAK LINGKUNGAN TERHADAP GAYA BICARA ANAK USIA 5-6 TAHUN DI TK NEGERI MELANGNUKU PETLENG - Yetimauh, Jublino Demokratini; Andreas Ande; Yohana Yuniati; Gokma N. Tampubolon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study identifies the environmental conditions in Petleng Village that shape the language development of 5–6 years old children at Melangnuku Petleng State Nursery School, in terms of the children’s speech patterns in everyday interactions, and analyses the relationship between the environment and these children’s communication skills. The research method employed was a descriptive qualitative approach, aimed at providing an in-depth description of the phenomena based on data collected in the field. The findings of this study indicate that the family, school and community environments all influence the development of speech styles in young children, albeit in different ways. The family plays a role in laying the foundations for children’s language skills and communicative behaviour. School helps to develop and guide these abilities through a structured learning process. Meanwhile, the community environment and social interactions influence how children express their emotions. Therefore, the development of children’s speech patterns is shaped through the combined influence of these three environments.